Optimization of CNTs production using full factorial design and its advanced application in protein purification - Mubarak, N. M.; Yusof, Faridah; Al-Khatib, Ma'an Fahmi Rashid; Ameen, Emad S.M; Khalid, M.; Al-Sa'adi, Abdul Razak Abdul Rahman Asaad; Atieh, Muataz A.; Qudsieh, Isam Y.; Walvekar, Rashmi Gangasa (World Scientific Publishing Co., 2010)
Carbon nanotubes (CNTs) have been successfully synthesized by using in-house fabricated Double Stage Chemical Vapor Deposition (DS-CVD) technique, using acetylene (C2H2) and hydrogen (H2) as the precursor gases. The purity, morphology and the structure of CNTs were then characterized using Field Emission Scanning Microscope (FESEM), Transmission Electron Microscope (TEM) and Thermogravimetric Analysis (TGA). The effects of the process parameters were examined whereby the experimental design of the investigation was conducted using Design Expert® Version 6.0.8. The statistical analysis reveals that the optimized conditions for the best CNTs yield production at 850°C reaction temperature, 60 min reaction time, with gas flow rates at 40 and 150 ml/min for C2H2 and H2, respectively. The CNTs produced were successfully used as column chromatographic media. Due to its nanosized structured dimension, CNTs' have tremendously large surface area and that lead to highly efficient protein purification. Skim latex protein has been used as the model protein and we aim to recover useful proteins and enzymes from this known wasteful material. During the purification, the process parameters such as pH and ionic strength of the running buffer were optimized to enhance protein purification. Results reveal that CNTs behave efficiently as a hydrophobic interaction chromatographic media.